Analisis Komoditas Basis dan Non Basis Sub Sektor Peternakan di Kecamatan Kusambi Kabupaten Muna Barat - Hildawati, Hildawati; Iswandi, R. Marsuki; Suriana, Suriana (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2018)
Livestock in Kusambi is one of the agriculture sub-sectors that have the largest production output among other sub-sectors. The present study aims to analyze the commodity which is base and non-base in Kusambi, West Muna and factors causing a commodity which is base and non-base in Kusambi, West Muna. The data of this study were typically secondary data. Data were analyzed by using Location Quotient, Dynamic Location Quotient, and descriptive analysis. The result showed that: (1) Livestock commodities that became the base in Kusambi were cattle, goat, chicken, and duck while the horse, buffalo, and domestic poultry were non-base commodities. (2) Livestock commodities that would be the present and the future bases were goat and chicken, non-base commodities in the present and in the future were a horse, buffalo, and domestic poultry, base commodities in the present but did not become base in the future were cattle, domestic poultry, and duck. (3) Factors causing livestock commodities being base and non-base was supported by internal and external factors. Internal factors as a base and non-base commodities were generally caused by high rate production, having experience in raising, large area, and stock. While external factors supporting commodities became base and non-base such as supply, a livestock facility, and infrastructure, climate, the selling price of the livestock, and government policy.